(untitled) (Revista Apotheke, 2025)
This essay is part of my master’s research and investigates montage as a central operation in my artistic process. The reflection begins with the image of a bed formed by the joining of two independent structures, a gesture that highlights the logic of bringing fragments together to produce new visual and symbolic relationships. Throughout the essay, I examine how this operation unfolds in my drawings, paintings, and mosaics, articulating procedures of juxtaposition, image collection, and the recombination of disparate parts. Montage is treated here as a method, a way of constructing images that do not seek continuous syntheses, but rather composite narratives made from encounters between autonomous elements. The essay discusses how the poetics of the fragment structures my work and how the gesture of joining becomes key to understanding the mobile, processual, and relational nature of these images.